The crisis of public health and infodemic: Analyzing belief structure of fake news about covid-19 pandemic - Kim, Seoyong; Kim, Sunhee (Sustainability (Switzerland), 2020)
False information about COVID-19 is being produced and disseminated on a large scale, impeding efforts to rapidly impose quarantines. Thus, in addition to the COVID-19 pandemic itself, an infodemic related with it is leading to social crises. This study therefore investigates who believes the misinformation that is being produced in the context of COVID-19. We choose two main factors—risk perception factor, so called psychometric paradigm, and communication factor—as independent variables that can affect belief in misinformation related to COVID-19. The results show that, among psychometric variables, perceived risk and stigma positively impact belief in fake news, whereas perceived benefit and trust have negative effects. Among communication factors, source credibility and the quantity of information reduce belief in fake news, whereas the credibility of information sources increases these beliefs. Stigma has the greatest explanatory power among the variables, followed by health status, heuristic information processing, trust, and subjective social class.
Keywords: Fake news; Infodemic; Misinformation; Risk communication; Risk perception